Analisis Kesiapan Sistem Remunerasi Berdasarkan Peraturan Gubernur Provinsi DKI Jakarta Nomor 222 Tahun 2016 Di RSUD Pesanggrahan Tahun 2017 - Dewi, Endah Kartika (UI Scholars Hub, 2017)
RSUD Pesanggrahan as a Health Service Unit of Special Capital Region of Jakarta which has applied financial pattern of Regional Public Service Board (BLUD). This research uses quantitative with simulation of system calculation to be applied and qualitative with explore stakeholder perception readiness with indepth interview. From the result of research it is known that in general the informant is satisfied with the income received now. And from the simulate conducted, RSUD Pesanggrahan has not been able to apply the system based on Governor Regulation No. 222/2016 yet. Suggestion to the Health Department as a regulator is to give the opportunity to the hosital that its BLUD income is capable to apply Remuneration system is supported by regulation, to evaluate the potential income of RSUD to make standard of employee performance target as indicator of hospital as some recommendation as a result from this research.